SOCIAL REPRESENTATION ABOUT ENTREPRENEURSHIP IN HIGH EDUCATION: AN EMPIRICAL STUDY ABOUT THE ACQUISITION OF ENTREPRENEURIAL SKILLS WITH PORTUGUESE NURSING STUDENTS - Parreira, Pedro Miguel Santos Dinis (2015)
BACKGROUND The social representations are socially produced that guide behavior and intervene in the individual and social identity. It is important to understand how the cognitive dimension is assimilated by entrepreneurship students and the changes that they are able to perform in the rational domain in the event of attending training sessions. AIM To describe the content and structure of the social representations of entrepreneurship among Portuguese students, before and after educational interventions. MATERIALS AND METHODS Qualitative research based on the Theory of Social Representations, in its structural approach, conducted at a higher education institution in Portugal (Coimbra). A population of 4th-year (final year) undergraduate nursing students in Portugal (Nursing School of Coimbra) was analyzed in two moments, 192 students in the first moment and 139 in the second moment. Participants were asked to answer the following question: "Write down the first five words or expressions that come to your mind when you read the word -Entrepreneurship. Answers were analyzed by specific software, the EVOC and SIMI software (Vèrges, 1993a), 2005 version, through the techniques developed by Vèrges (1987-1994). RESULTS The results indicate stabilization in both structures of representations. However, the prototypical categorization highlighted a richer and more organized structuring of students after the training sessions in entrepreneurship. This structure was more in line with the concepts of entrepreneurship, from the idea to business, where a path to success is visible. Concepts such as dynamism, research, discovery, proactivity, taking a risk, challenge, commitment, ambition, bet, and challenge emerged in a second periphery and, therefore, it is necessary to invest even more in training, thus stimulating the need for determination to undertake. CONCLUSIONS A consistency in the formative and learning processes was observed, consistent with the dimensions of concepts considered as important to undertake. Positive attitudes emerged that guided the representation under study, in line with the development of the core competencies to undertake.